Placebo Response in Pediatric Anxiety Disorders: Implications for Clinical Trial Design and Interpretation - Dobson, Eric T. (J Child Adolesc Psychopharmacol, 2016)
Objectives: The characterization and prediction of placebo response in clinical trials of youth with anxiety disorders have received little attention, despite the critical effects of placebo response rate on the success or failure of clinical trials. With this in mind, we sought to examine the factors that predict or influence placebo response in randomized controlled trials of youth with anxiety disorders. Methods: Prospective, randomized, parallel-group controlled trials of psychopharmacologic interventions in pediatric patients with anxiety disorders were identified using a search of PubMed/Medline (1966–2015). Weighted least squares regression models and z-tests were utilized to examine the impact of continuous and categorical variables, respectively, on placebo response. These variables included demographic (e.g., age, percent white, percent female), clinical (e.g., baseline symptom severity), and trial characteristics (sample size, duration, funding). Finally, the relationship between the class of comparator medication and placebo response rate was examined using a multiple comparison for proportions test. Results: The analyses of data from 14 trials involving 2230 patients and 9 medications reveal that higher placebo response rates were associated with a greater number of study sites (p = 0.013) and fewer patients per site (p < 0.008), while placebo dropout rates increased with more recent publication (p = 0.01) and were positively associated with the number of study visits (p < 0.02). Lower placebo response rates were associated with federally funded studies (z = −4.61, p < 0.001), studies conducted in the United States (z = 1.81, p < 0.035), and with an increased likelihood of detecting a significant effect on the primary outcome (z = 4.58, p < 0.0001). Additionally, studies, in which the majority of patients (>60%) had a diagnosis of social anxiety disorder, exhibited lower placebo response rates (p < 0.001). Finally, for trials, effect size has decreased over time (p = 0.004). Conclusions: Important trial-specific factors affect placebo response and placebo dropout in youth with anxiety disorders and have pragmatic implications for the conduct and design of clinical trials and raise the possibility that limiting the number of sites while maximizing the number of patients per site could enhance the ability to detect medication–placebo differences.